REINVENTING PERGURUAN TINGGI DALAM BLUE OCEAN STRATEGY (Suatu Studi Analisis teoritik) - Gusti Irhamni (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2017)
The status of college which is social/nonprofit which means not profit oriented to many universities to enliven its social character, only get the receipt of money from Education Development contribution (SPP) of students, the obstacle is if the students are few, so the budget for the cost of Tri Dharma can be disrupted when the function of universities is to implement Tri Dharma.Reinventing is allowed as long as it is nonprofit because the profits earned are used for institutional development, not for the personal benefit of foundations and lecturers. While the purpose of this research is to know the role of reinventing in developing universities and developing reinventing colleges by establishing Blue Ocean Strategy.The research methodology used by using descriptive qualitative approach, that is using empirical experiences and sources of secondary data/literature.The result of this research is that universities especially (PTS) are non profit/ social, which rely solely on the receipt of money SPP students, so PTS less developed, then PTS in the need to open additional branches of business/business/reinventing. The reinventing remains a nonprofit status because of the profit gained for institutional development.Private universities (PTS) have advantages: technology, human resources, and market segment such as: students, lecturers, alumni/family (alma mater) so that they can move in blue ocean strategy.